2020
DOI: 10.1111/jnc.15132
|View full text |Cite
|
Sign up to set email alerts
|

To Ub or not to Ub: Regulation of circadian clocks by ubiquitination and deubiquitination

Abstract: Circadian clocks are internal timing systems that enable organisms to adjust their behavioral and physiological rhythms to the daily changes of their environment. These clocks generate self‐sustained oscillations at the cellular, tissue, and behavioral level. The rhythm‐generating mechanism is based on a gene expression network with a delayed negative feedback loop that causes the transcripts to oscillate with a period of approximately 24 hr. This oscillatory nature of the proteins involved in this network nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 167 publications
(257 reference statements)
0
18
0
Order By: Relevance
“…In cells, deubiquitination enzymes work by removing ubiquitin tags from tagged proteins or reducing the length of polyubiquitin tags [ 49 ]. The balance between ubiquitination and deubiquitination affects physiological protein abundance and activity [ 61 ]. The critical role of the Lys48 and Lys63 linker chains in cell signaling has been well documented in many studies; in contrast to “atypical” chain types such as Lys6, Lys11, Lys27, Lys29, Lys33 or Met1, there are few reports, but a few studies have found that the physiological role of these atypical chains is also obvious [ 62 , 63 , 64 , 65 ].…”
Section: Ubiquitination Is Essential For the Pathophysiological Regul...mentioning
confidence: 99%
“…In cells, deubiquitination enzymes work by removing ubiquitin tags from tagged proteins or reducing the length of polyubiquitin tags [ 49 ]. The balance between ubiquitination and deubiquitination affects physiological protein abundance and activity [ 61 ]. The critical role of the Lys48 and Lys63 linker chains in cell signaling has been well documented in many studies; in contrast to “atypical” chain types such as Lys6, Lys11, Lys27, Lys29, Lys33 or Met1, there are few reports, but a few studies have found that the physiological role of these atypical chains is also obvious [ 62 , 63 , 64 , 65 ].…”
Section: Ubiquitination Is Essential For the Pathophysiological Regul...mentioning
confidence: 99%
“…Numerous studies have shown that ubiquitination, occupies a prominent place in the turnover of circadian clock proteins [15]. Ubiquitination is a proteolytic pathway whereby targets are polyubiquitinated by covalent attachments of ubiquitin chains of 76 amino acid monomers which flag the substrate for cleavage into constituent amino acids, mediated by the 26S proteasome complex [16,17].…”
Section: Ubiquitinationmentioning
confidence: 99%
“…The timing and robustness of this circadian clockwork is aided by post-transcriptional and post-translational modifications mediated by many enzymes such as kinases, phosphatases, acetyl transferases, ubiquitin ligases, etc. 1,5 The circadian clockwork regulates various cellular and physiological processes via the control of the expression of clock-controlled genes (CCGs). Transcription factors such as CLOCK/BMAL1 or REV-ERBα bind numerous genes besides their targets within the clock.…”
Section: Introductionmentioning
confidence: 99%
“…These negative and positive feedback loops act temporally in such a manner that the transcripts and proteins encoded by many of the clock genes show a ~24‐h variation in their abundance. The timing and robustness of this circadian clockwork is aided by post‐transcriptional and post‐translational modifications mediated by many enzymes such as kinases, phosphatases, acetyl transferases, ubiquitin ligases, etc 1,5 …”
Section: Introduction: Circadian Rhythms In the Immune Systemmentioning
confidence: 99%